Effect of MoO HTL on the Performance of ITO/ZnO CQDs/F8BT:TIPS-Pentacene/MoO/Ag UV-Visible Photodetector - Pratap Singh A.; Tripathi S.; Jit S. (My University, 2025)
The n-type zinc oxide (ZnO) colloidal quantum dots (CQDs) and p-type blended poly(9,9-dioctylfluorene-alcohol-benzothiadiazol) (F8BT):6,13-bis (tri-isopropyl-silylethynyl) pentacene (TIPS-P) nanocomposite-based heterojunction fabricated on indium tin oxide (ITO)-coated substrate are explored for ultraviolet (UV)-visible photodetection. The effect of MoO3 hole-transporting layer (HTL) on the performance of the proposed ITO/ZnO CQDs/F8BT:TIPS-P/MoO3/Ag photodetector structure has been investigated. Under -1 V reverse bias, the maximum responsivity and specific detectivity were improved in the UV region from 29.60 to 70.20 A/W and from 6.35 × 1012 Jones to 3.97 × 1013 Jones at 385 nm (17.43μ W/cm2 intensity), respectively, by using the MoO3 HTL in the device. On the other hand, the maximum responsivity and specific detectivity were improved, respectively, from 13.68 to 40.92 A/W and from 2.93 × 1012 to 2.08 × 1013 Jones in the visible region at 470 nm (35.94μ W/cm2 intensity) due to the use of the MoO3 HTL under -1 V reverse bias. © 1963-2012 IEEE.